Contextual Teaching Materials Development and Its Impact on Science Learning Outcomes - Maryunita Maryunita; Helmi Helmi; Muhammad Arsyad (Journal La Edusci, 2026)
This study aimed to develop contextual-based science teaching materials on the topic of pressure and to evaluate their validity, practicality, and effectiveness in improving students’ science learning outcomes at YHS Christian Junior High School Makassar. The study employed a Research and Development (R&D) approach using the 4-D model, consisting of the Define, Design, Develop, and Disseminate stages. The effectiveness of the developed teaching materials was examined using a quasi-experimental design involving an experimental group and a control group. The field testing involved 30 Grade IX students, consisting of 16 students in the experimental group and 14 students in the control group. Data were collected using expert validation sheets, teacher practicality questionnaires, and students’ learning achievement tests. The validation results indicated that the developed teaching materials achieved an average Aiken’s V coefficient of 0.90, indicating high validity. The practitioners’ evaluation yielded an average practicality score of 92.91%, categorizing the teaching materials as very practical. The effectiveness analysis showed that students who learned using contextual-based teaching materials achieved higher learning outcomes than those who learned using conventional teaching materials. The Independent Samples t-test revealed a calculated t-value of 6.15, which exceeded the critical t-value of 1.40 at the 5% significance level, indicating a statistically significant difference between the two groups. These findings demonstrate that the developed contextual-based science teaching materials are valid, practical, and effective in improving junior high school students’ science learning outcomes.